2009
DOI: 10.1038/ijo.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Circulating soluble transferrin receptor concentration decreases after exercise-induced improvement of insulin sensitivity in obese individuals

Abstract: Background: Circulating soluble transferrin receptor (sTfR) has been recently found to be associated negatively with insulin sensitivity. Objective: To evaluate circulating sTfR concentration after changing insulin sensitivity in obese individuals. Design: Circulating sTfR concentration was evaluated after diet-induced weight loss in obese women (diet (D) group, n ¼ 8); after diet-induced weight loss plus resistance training (D þ RT group, n ¼ 11); and after follow-up without weight loss (control (C) group, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…The finding of strong sTfR association with fasting insulin and HOMA-IR without finding consistent associations with hyperglycemia suggests a reverse causation scenario, with high sTfR levels being caused by high insulin levels in an insulin-resistant state. This would be in line with the observation of Fernandez-Real et al (38), who observed a decrease in sTfR concentration after exercise-induced improvement of insulin sensitivity in 26 obese women.…”
Section: Stfr and Stfr-f-indexsupporting
confidence: 91%
“…The finding of strong sTfR association with fasting insulin and HOMA-IR without finding consistent associations with hyperglycemia suggests a reverse causation scenario, with high sTfR levels being caused by high insulin levels in an insulin-resistant state. This would be in line with the observation of Fernandez-Real et al (38), who observed a decrease in sTfR concentration after exercise-induced improvement of insulin sensitivity in 26 obese women.…”
Section: Stfr and Stfr-f-indexsupporting
confidence: 91%
“…When obese subjects were submitted to a diet and exercise program resulting in weight loss, circulating sTfR significantly decreased, and this decrease was proportional to changes in muscle volume and leg and arm force. Weight loss induced by diet alone did not affect circulating sTfR (37).…”
Section: Iron and Muscle Relationships With Glucose Homeostasismentioning
confidence: 71%
“…Clinical studies have reported positive association of serum osteocalcin level with insulin sensitivity and secretion in normal subjects (24) and in patients with type 2 diabetes (49,50). Clinical studies have reported positive association of serum osteocalcin level with insulin sensitivity and secretion in normal subjects (24) and in patients with type 2 diabetes (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Kanazawal and colleagues (21) demonstrated that osteocalcin levels nega-tively correlated with fasting plasma glucose, hemoglobin A1c, percent fat, pulse wave velocity, and intima to media thickness. A Spanish study (24), performed in a cross sectional study of adult men and women who experienced weight loss with or without exercise, found that circulating osteocalcin was associated with insulin sensitivity and insulin secretion. Similar observations were reported in groups of postmenopausal women (23).…”
mentioning
confidence: 99%